Changes in Risk Management on Financial Sector After February 2022 : Changes and drivers for changes in risk management on financial sector after Russia’s full-scale invasion of Ukraine - Pusa, Ville (My University, 2026)
The purpose of this master's thesis is to examine how risk management practices have changed in the European financial sector since Russia launched a full-scale war of aggression in February 2022. The research focuses in particular on Finnish financial sector actors and how the geopolitical uncertainty caused by the war has affected risk management priorities, processes and operating methods. The aim of the research is to determine what changes have been observed in financial sector risk management since 2022 and through what channels the most significant changes have occurred. The theoretical framework of the thesis is based on comprehensive risk management of companies, institutional theory and organizational resilience. The perspectives examine geopolitical risk both as an external change in the operating environment and as a factor that can be transmitted to financial sector organizations through existing risk areas. The study was conducted as a qualitative study, and empirical data was collected through five anonymized semi-structured expert interviews. The interviewees worked in Finnish financial sector organizations in risk management-related tasks. The data was analyzed using thematic analysis. The results of the study show that risk management has changed since February 2022, but the change has not been uniform in all risk areas. The most obvious changes were related to sanctions compliance, combating financial crime, customer risk management, operational resilience, cyber risks, outsourcing, security and reporting. In particular, the sanctions against Russia and Belarus required financial sector actors to make rapid process changes and monitor them more closely than before. The importance of operational risk management also increased, as the geopolitical situation increased attention to cybersecurity, continuity planning, external service providers and crisis preparedness. For traditional financial risks, such as market, credit, liquidity and capital risks, the study does not show a single significant change in risk management processes. Existing tools and processes in these areas were considered to be largely ready for change, but the importance of monitoring and reporting increased in the changed operating environment. Based on the study, the war acted more as a factor that accelerated and strengthened certain areas of risk management than as a reformer of risk management in the financial sector as a whole. The study complements previous research by showing how geopolitical risk is transmitted to the financial sector’s internal risk management practices. From a practical perspective, the results highlight the importance of monitoring, reporting, sanctions control and operational resilience in a geopolitically uncertain operating environment. However, the results of the study should be interpreted as qualitative observations, as the data is based on five expert interviews.
Keywords: risk management; financial sector; geopolitics; financial institutions; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development